2020
DOI: 10.1007/s00190-019-01330-1
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up PPP ambiguity resolution using triple-frequency GPS/BeiDou/Galileo/QZSS data

Abstract: Precise point positioning (PPP) has been suffering from slow convergences to ambiguity-fixed solutions. It is expected that this situation can be relieved or even resolved using triple-frequency GNSS data. We therefore attempt an approach where uncombined triple-frequency GPS/BeiDou/Galileo/QZSS (Quasizenith satellite system) data are injected into PPP, whereas their raw ambiguities are mapped into the extra-wide-lane, wide-lane and narrow-lane combinations for integer-cycle resolution at a single station (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 37 publications
0
35
0
1
Order By: Relevance
“…On the contrary, Li et al (2018) implemented BeiDou-only PPP-AR using triple-frequency data and decreased the convergence time by 10% compared to that of dual-frequency ambiguity-fixed solutions. Using triplefrequency GPS/BeiDou/Galileo/QZSS (Quasi-Zenith Satellite System) data, ultimately, Geng et al (2019b) achieved PPP-AR with a mean time of about 6 minutes. However, such a few minutes of convergence time still does not fit autonomous driving demanding super high availability of accurate positions, especially in urban valleys where loss of satellite signals takes place frequently.…”
Section: Using Realmentioning
confidence: 99%
“…On the contrary, Li et al (2018) implemented BeiDou-only PPP-AR using triple-frequency data and decreased the convergence time by 10% compared to that of dual-frequency ambiguity-fixed solutions. Using triplefrequency GPS/BeiDou/Galileo/QZSS (Quasi-Zenith Satellite System) data, ultimately, Geng et al (2019b) achieved PPP-AR with a mean time of about 6 minutes. However, such a few minutes of convergence time still does not fit autonomous driving demanding super high availability of accurate positions, especially in urban valleys where loss of satellite signals takes place frequently.…”
Section: Using Realmentioning
confidence: 99%
“…We reasonably consider this a natural choice for a multitude of reasons. First, the combination E1+E5a is the most commonly used dual-frequency combination in Galileo related studies, see, e.g., [8,10,12,19], while these frequencies allow for the interoperability of GPS and Galileo in mixed-system positioning due to the overlapping frequencies L1/E1 and L5/E5a [47]. Moreover, most of the MGEX analysis centres provide E1/E5a-based ionosphere-free clock products for the Galileo satellites [48].…”
Section: Frequency Spacingmentioning
confidence: 99%
“…In particular, the integration of multi-frequency data increases the model's redundancy and provides a stronger positioning model, which will improve ambiguity resolution and, therefore, the user-convergence. Experimental studies have demonstrated that the addition of a third frequency (GPS L5, Galileo E5b, BeiDou B3) reduces the time-to-fix-ambiguities and convergence times using data from GPS [15], Galileo [16,17], GPS and Galileo [9], Galileo and BeiDou [18], GPS, BeiDou, Galileo and QZSS combined [19].…”
Section: Introductionmentioning
confidence: 99%
“…Also Management and competencies that the introduction of the private sector to public services, and the involvement of e in risk tolerance . and Achieve better value for money in public spending: (Geng et al, 2020) Meaning the optimal price for the customer on the basis of cost over the term of the contract, the quality of service provided, and the risks borne by the participant . The total price of the public and private sector tender submitted by the partner should be less than the cost that the government would bear if it provided the same level of service, including the additional costs of risks ( cost overruns -delays ... etc ) that the government would face.…”
Section: Objectives Of Pppmentioning
confidence: 99%